A Novel Boost Cascaded Multilevel Inverter - Lee, Sze Sing; Yang, Yongheng; Siwakoti, Yam Prasad; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2021)
This article presents a novel cascaded multilevel inverter as an alternative to the cascaded H-bridge (CHB). By adopting two H-bridges integrated with two inductors and two power switches, the proposed topology is able to generate a five-level voltage with merely a single dc source. Voltage-boosting capability is guaranteed despite its single-stage operation. A corresponding modulation technique is also established to charge the boost inductors with a constant duty-cycle while simultaneously generating a five-level ac voltage. Therefore, the proposed topology outperforms the CHB in reducing the isolated dc source count, enhancing the voltage gain, and lowering the dc source voltage magnitude. In addition, the modularity is preserved, where the proposed topology can be extended by cascading multiple modules. The operation and feasibility of the proposed cascaded multilevel inverter is analyzed and validated through simulation and experimental results.
Keywords: Boost inductors; Cascaded H bridge (CHB); Cascaded multi-level inverters; Modulation techniques; Power switches; Single dc source; Two inductors; Voltage boosting; Boost inverter; cascaded multilevel inverter; five level; voltage boosting